Overview of HSV infection: an integrative literature review (Research, Society and Development, 2022)
The present research aims to carry out an integrative review of the literature regarding the infection by the herpes viruses (HSV-1 and HSV-2), aiming at the elucidation of clinical aspects and complications associated with the infection, as well as the presentation of epidemiological data, forms of transmission, characteristics of the pathogen, and the development of vaccines, discussed superficially in this review. In addition, data on the disease in Brazil are presented between January 2019 and April 2020 and between January 2021 and April 2022. The international databases PubMed, SciELO and LILACS were used during the searches, as well as information from the World Health Organization were selected. Thus, 30 scientific articles were selected to compose the bibliographic base of the current review, according to the pre-established inclusion and exclusion criteria.